Development of an electrically conductive polymer composite based on linear low-density polyethylene modified with high-structural carbon black - E. A. Rogachev; A. A. Kalenchuk (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The developed polymer composites based on low-density linear polyethylene modified with OMCARB CH85 technical carbon have been experimentally investigated. A comprehensive analysis of the composites' properties has demonstrated that the use of this filler type results in a percolation transition at a 25 % mass fraction of filler, leading to an decrease in resistivity. Samples with lower concentrations exhibit electrical resistance values corresponding to those of semiconductors. When the filler concentration reaches 20 %, the maximum material stiffness is observed, and the character of stretching transitions from ductile to brittle. Electron microscopic examination of the samples reveals a mesh microstructure of the polymer matrix with embedded carbon black particles acting as crystallization nuclei. As a result, the mechanical properties and electrical conductivity of the composite are enhanced.